Solving sqrt(1+sqrt(x)) = x-1in Two Ways

preview_player
Показать описание
If you need to post a picture of your solution or idea:
#ChallengingMathProblems #RadicalEquations

PLAYLISTS 🎵 :

Рекомендации по теме
Комментарии
Автор

In your first method, you can probably reject (1-√5)/2 sooner (as a candidate value for √x) because √x is expected to be non-negative by convention.

PS-mhts
Автор

I did kind of a mix of both methods:
1. Squaring both sides
2. Sub sqrt(x) = u
Then we get u=0, which we can reject as it isnt in our domain
Then we can factor the rest in u+1 and u^2-u-1 which solutions we have seen in the video

marcusorban
Автор

10:25 But √1 is equal to both 1 and -1
Why can't you let x=1 and take the negative answer to the second square root? √(1+√1)=1-1 --> √(1+(-1))=1-1 --> √0=0

adipy
Автор

substituting y = 1+√x in the original equation gives x = 1+√y

this is an inolution of an increasing function. setting y=x gives x = 1+√x or
x -√x - 1 = 0, a quadratic in √x with + root φ.
x = φ² = φ+1

echandler
Автор

Finally I solved my first problem on this channel

madhurkenge
Автор

Actually all four roots of the quartic i.e. x=0, x=1, x=(3+/-sqrt(5))/2 fulfil the condition with some choices of sign for the square root terms. For me, negative square roots of reals are permitted, like we use in the quadratic formula.

pwmiles
Автор

Finally something that i can solve about Sybermath's problems.

konoveldorada
Автор

At 4.39 you have 1 + sqrt(x) = x. This can be solved directly by the quadratic formula by putting x as (sqrt(x))^2, i. e. (sqrt(x))^2 - sqrt(x) - 1 = 0, thus sqrt(x) = (1 + or - sqrt(5))/2, squaring this:
x = (3 + or - sqrt(5))/2. (Or use subst. u = sqrt(x), u^2 = x, 1 +u = u^2, ...)

l.h.
Автор

1. By adding one to both sides we get
x=1+sqrt(1+sqrt(x))
2. Substituting x into the right side we get

3. Doing 2 for many times we get

So we know
x=1+sqrt(x)
3. Solve the above equation

CKth
Автор

*some madlad just straight up using the cubic quadratic formula*

axbs
Автор

4:06 who else is disappointed that Syber didn't say "keepin' it real"?

armacham
Автор

If we call the golden ratio phi, the solution to the problem is x = phi^2 . Remember that phi^2=phi+1 . When we substitute x=phi^2 into our original equation we get phi on the left side and phi on the right side . We therefore get that x = phi^2 is a solution . Of course this is in hind site . In reality I solved this problem the hard way before I watched the video . I solved a cubic by Cardano's formula, and then I recognized that the decimal value was phi^2 .

pk
Автор

it is the loop equasion. solved by using a cycle
the equasion os √(1+√1+√...) = √x. or shorting the loop √(1+√x) = √x. or

cicik
Автор

I am SO glad that you do not square both sides at the start. You always try to work around that and that’s something I do too. Squaring both sides might turn out to be extremely bad, not only because you miss a solution, but because it also makes things worse to solve, most of the time.

larzcaetano
Автор

6:14 (1-sqrt(5))/2 is negative and cannot be equal to sqrt(x)

benardolivier
Автор

The both methods are excellent. But there is the third method.

AntonNazoev
Автор

As for the check of the solutions, if you are Japanese, like √ 2, √ 3, √ 7, you remember √ 5 = 2.2360679 in Goro-awase - mnemonic system using the similarity between numbers and words, so (3-√5) / 2 ≒(3-2.236) / 2 = 0.764/2 =0.382<1, (3+√5)/2≒(3+2.236)/2=5.236/2=2.618>1, (3-√5)/2 will be written as unsuitable, and (3+√5)/2 is appropriate.

wuhyltw
Автор

Wow, I can solve cubic equation and others through your algebraic manipulations, u guys are amazing

samuelbassey
Автор

x^3-4x^2+4x-1 = 0 is hemisymmetric, odd degree. These always have a root of 1.

septembrinol
Автор

Awesome, substitution is so powerful, it make the problem more organized, good job

tonyhaddad